Company Value: The Effect of Intellectual Capital, Information Transparency, and Company Size - Leny Suzan; Erfa Fauzi (Jurnal ASET (Akuntansi Riset), 2024)
This research aims to analyze the relationship between intellectual capital (IC), information transparency, company size, and company value in banking companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. This research uses quantitative methods and panel data regression using Eviews 12 to test the relationship between research variables. The sampling technique was carried out using a purposive sampling method to obtain forty companies as research samples. The results of this research show that intellectual capital has a positive effect on company value, this shows that increasing intellectual capital (IC) can increase company value. The company value is not affected by information transparency. The company value is not affected by the size of the company. The information asymmetry between investors and managers explains a relationship between company value and signal theory. Companies with high intellectual capital have a competitive advantage in attracting investors' attention and can increase company value. The implications of this research are shown to companies, investors, and future researchers. This research provides new insight into the relationship between the influence of intellectual capital (IC), information transparency, and company size on company value in banking companies listed on the Indonesia Stock Exchange from 2018 to 2022.